2021
DOI: 10.20892/j.issn.2095-3941.2021.0052
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of characteristics and predictive factors of immune checkpoint inhibitor-related adverse events

Abstract: Objective: We aimed to retrospectively analyze the toxicity profiles and predictors of immune-related adverse events (irAEs) as well as the correlation between irAEs and the clinical efficacy of multi-type immune checkpoint inhibitors (ICIs) in patients with advanced pan-cancer in a real-world setting. Methods: We retrospectively analyzed data from 105 patients with advanced pan-cancer treated with multi-type ICIs at the First Hospital of Jilin University between January 1, 2016 and August 1, 2020. We used log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 44 publications
(53 reference statements)
4
20
0
Order By: Relevance
“…The types of blood counts reported are as follows: absolute eosinophil count (AEC), derived neutrophil: lymphocyte ratio (dNLR), neutrophil: lymphocyte ratio (NLR), absolute neutrophil count (ANC), absolute lymphocyte count (ALC), absolute monocyte count (AMC), platelet count (PLT), monocyte: lymphocyte ratio (MLR), platelet: lymphocyte ratio (PLR), etc. Eight studies showed substantial truncation values ( 11 , 15 17 , 20 , 23 , 25 , 28 ). Eleven studies reported the use of receiver operating characteristic (ROC) curve analysis to calculate the optimal cutoff value ( 11 , 15 17 , 19 21 , 23 26 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The types of blood counts reported are as follows: absolute eosinophil count (AEC), derived neutrophil: lymphocyte ratio (dNLR), neutrophil: lymphocyte ratio (NLR), absolute neutrophil count (ANC), absolute lymphocyte count (ALC), absolute monocyte count (AMC), platelet count (PLT), monocyte: lymphocyte ratio (MLR), platelet: lymphocyte ratio (PLR), etc. Eight studies showed substantial truncation values ( 11 , 15 17 , 20 , 23 , 25 , 28 ). Eleven studies reported the use of receiver operating characteristic (ROC) curve analysis to calculate the optimal cutoff value ( 11 , 15 17 , 19 21 , 23 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies showed substantial truncation values ( 11 , 15 17 , 20 , 23 , 25 , 28 ). Eleven studies reported the use of receiver operating characteristic (ROC) curve analysis to calculate the optimal cutoff value ( 11 , 15 17 , 19 21 , 23 26 ). In all included reports, skin adverse reactions were the most common (23.34%), followed by endocrine adverse reactions (22.81%), immune pneumonia (13.50%), hepatic adverse reactions (10.25%), and gastrointestinal adverse reactions (9.23%).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that patients with preexisting autoimmune diseases are at an increased risk of experiencing flare-ups following ICB administration [ 11 ]. Similarly, personal and familial histories of psoriasis are significant predictors of psoriasis development following ICB treatment [ 12 ].…”
Section: Cutaneous Iraes In Melanoma Patientsmentioning
confidence: 99%
“…The most common immune-associated adverse events (AEs) were of grade 1-2: 8 patients had skin responses, 2 of which were of grade 3 or 4, and all others were of grade 1 or 2, with rash being the most common AE; 3 patients had endocrine AEs (mainly hypothroidism/hyperthroidism), and one patient had grade 4 hemorrhage, which might have been associated with apatinib. Some parameters that may be potential predictive biomarkers of immune-associated AEs in clinical practice, especially when immune checkpoint inhibitors are combined with chemotherapy and or targeted drugs 21 .…”
Section: New Exploration Of the Four-drug Model In The Era Of Immunot...mentioning
confidence: 99%